2017
DOI: 10.1002/cepa.244
|View full text |Cite
|
Sign up to set email alerts
|

08.19: Tests on concrete‐filled double skin tubular beams with circular stainless steel outer tubes

Abstract: A test program on concrete-filled double skin tubular (CFDST) beams with austenitic stainless steel outer tubes and high strength steel inner tubes is presented in this paper. A total of 22 four-point bending tests was carried out to study the behaviour and strengths of CFDST beams. The stainless steel outer tubes were circular hollow sections (CHS) with average diameter-to-thickness ratios of 56.8 and 48.5, and the measured 0.2% proof strengths of 276 MPa and 300 MPa, respectively. The high strength steel inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Test results showed that the flexural resistance of CFDST members was higher compared to CFST members. Furthermore, Uneka et al, 28 Wang et al, 29 Li et al, 26 Zhao et al, 30 Wang et al, 31 and Wang et al 32 studied the performance of double‐skin concrete‐filled steel tubular (DCFST) members with an inner hollow tube under different loading conditions including flexural load. However, due to the presence of the hollow inner tube, the performance of the DCFST member is different from its CFDST counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Test results showed that the flexural resistance of CFDST members was higher compared to CFST members. Furthermore, Uneka et al, 28 Wang et al, 29 Li et al, 26 Zhao et al, 30 Wang et al, 31 and Wang et al 32 studied the performance of double‐skin concrete‐filled steel tubular (DCFST) members with an inner hollow tube under different loading conditions including flexural load. However, due to the presence of the hollow inner tube, the performance of the DCFST member is different from its CFDST counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…By using finite element analysis (FEA), Huang [10] investigated the effects of important parameters which are used to determine sectional capacities of CFDST stub columns. In the other hand, many researchers have investigated the CFDST subjected to only pure bending [11][12][13][14][15], however, comprehensive studies in ultimate bending moment of CFDST, especially with a full scale CFDST, have not been reported so far.…”
Section: Introductionmentioning
confidence: 99%